2022
DOI: 10.1037/xhp0000997
|View full text |Cite
|
Sign up to set email alerts
|

Orthographic neighborhood effects during lateralized lexical decision are abolished with bilateral presentation.

Abstract: Words presented to the right visual field (RVF) are processed more rapidly than those in the left visual field (LVF), presumably because of more direct links to the language dominant left cerebral hemisphere. This effect is moderated by a word's orthographic neighborhood size (N), with LVF facilitation and RVF inhibition for words with a large N. Across two experiments, we sought to further examine lateralized N effects. Experiment 1 examined how hemispheric dominance for language influenced lateralized N effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…First, the experiments were conducted entirely online, limiting experimental control over participants’ viewing conditions, hardware, operating system, or browser, which all can potentially affect timing performance. However, recent studies have demonstrated comparable performance in online and laboratory studies of lateralized word processing (Mills et al, 2022; Parker et al, 2021; Veldre et al, 2022) and masked priming (Angele et al, 2022), suggesting that online data collection is suitable for paradigms requiring precise timing.…”
Section: Discussionmentioning
confidence: 99%
“…First, the experiments were conducted entirely online, limiting experimental control over participants’ viewing conditions, hardware, operating system, or browser, which all can potentially affect timing performance. However, recent studies have demonstrated comparable performance in online and laboratory studies of lateralized word processing (Mills et al, 2022; Parker et al, 2021; Veldre et al, 2022) and masked priming (Angele et al, 2022), suggesting that online data collection is suitable for paradigms requiring precise timing.…”
Section: Discussionmentioning
confidence: 99%
“…The use of bilateral presentation had several advantages in the context of the current experiment compared to unilateral presentation: (1) it enabled direct comparison with Oltedal and Hugdahl (2017) who also employed bilateral presentation for the visual presentation of consonant-vowel strings; (2) its adoption allows a more direct parallel (compared to unilateral visual presentation) between the visual and the auditory modality, as bilateral visual presentation elicits competition between LVF and RVF (Hunter & Brysbaert, 2008;Hausmann et al, 2019); (3) it followed from Hunter and Brysbaert's (2008) observation that divided visual field reading effects are larger and more stable when bilateral presentation is adopted instead of unilateral presentation (Boles, 1987(Boles, , 1990(Boles, , 1994; see also Iacoboni & Zaidel, 1996; for more recent applications of this technique, see Willemin et al, 2016, Hausmann et al, 2019, and Mills et al, 2022; and (4) in the absence of explicit fixation control via eye tracking, the use of bilateral presentation can (by virtue of competition for attentional resources) reduce the probability of eye movements (Hunter & Brysbaert, 2008).…”
Section: Visual Half-field Tasksmentioning
confidence: 99%
“…While the corpus callosum does allow for the transfer of information between the hemispheres, there is more efficient processing for linguistic stimuli arriving at the left hemisphere as there is an absence of transfer/processing costs from the non-dominant to the language dominant hemisphere (Bonandrini, Paulesu et al, 2023;Bourne, 2006;Hellige, 1993;Hunter & Brysbaert, 2008). It is not surprising then that many studies have produced a strong RVF advantage for the processing of written words (e.g., Bonandrini, Paulesu et al, 2023;Brederoo et al, 2019Brederoo et al, , 2020Hausmann et al, 2019;Mills et al, 2022;Parker et al, 2020;Perea et al, 2008;Willemin et al, 2016) despite using very different stimuli between studies.…”
mentioning
confidence: 99%